Impact of Rape Reform Legislation in Six Major Urban Jurisdictions in the United States, 1970-1985 - Horney, Julie ([Verlag nicht ermittelbar], 1998)
Despite the fact that most states enacted rape reform legislation by the mid-1980s, empirical research on the effect of these laws was conducted in only four states and for a limited time span following the reform. The purpose of this study was to provide both increased breadth and depth of information about the effect of the rape law changes and the legal issues that surround them. Statistical data on all rape cases between 1970 and 1985 in Atlanta, Chicago, Detroit, Houston, Philadelphia, and Washington, DC, were collected from court records. Monthly time-series analyses were used to assess the impact of the reforms on rape reporting, indictments, convictions, incarcerations, and sentences. The study also sought to determine if particular changes, or particular combinations of changes, affected the case processing and disposition of sexual assault cases and whether the effect of the reforms varied with the comprehensiveness of the changes. In each jurisdiction, data were collected on all forcible rape cases for which an indictment or information was filed. In addition to forcible rape, other felony sexual assaults that did not involve children were included. The names and definitions of these crimes varied from jurisdiction to jurisdiction. To compare the pattern of rape reports with general crime trends, reports of robbery and felony assaults during the same general time period were also obtained from the Uniform Crime Reports (UCR) from the Federal Bureau of Investigation when available. For the adjudicated case data (Parts 1, 3, 5, 7, 9, and 11), variables include month and year of offense, indictment, disposition, four most serious offenses charged, total number of charges indicted, four most serious conviction charges, total number of conviction charges, type of disposition, type of sentence, and maximum jail or prison sentence. The time series data (Parts 2, 4, 6, 8, 10, and 12) provide year and month of indictment, total indictments for rape only and for all sex offenses, total convictions and incarcerations for all rape cases in the month, for those on the original rape charge, for all sex offenses in the month, and for those on the original sex offense charge, percents for each indictment, conviction, and incarceration category, the average maximum sentence for each incarceration category, and total police reports of forcible rape in the month. Interviews were also conducted in each site with judges, prosecutors, and defense attorneys, and this information is presented in Part 13. These interviewees were asked to rate the importance of various types of evidence in sexual assault cases and to respond to a series of six hypothetical cases in which evidence of the victim's past sexual history was at issue. Respondents were also presented with a hypothetical case for which some factors were varied to create 12 different scenarios, and they were asked to make a set of judgments about each. Interview data also include respondent's title, sex, race, age, number of years in office, and whether the respondent was in office before and/or after the reform.